Physical rehabilitation and Rehabilitation of Children with Cerebral Palsy, Organization of Psychological Services Parent Support. - Alimova Iroda Anvarovna; Raiimova Zulfiya Mahamatjonovna (Zien Journals, 2023)
Organization and improvement of medical-rehabilitation, psychological and pedagogical assistance to children with cerebral palsy in the information consulting service of the Fergana branch of the RCSAD. Organization of a service of psychological and methodological support to parents
Keywords: Rehabilitation; service; parents